Modeling the impacts of technological innovation and financial development on environmental sustainability: New evidence from the world's top 14 financially developed countries - Assad Ullah; Mesut Dogan; Betul Altay Topcu; Haifa Saadaoui (Energy Strategy Reviews, 2023)
Developing a sustainable economic system in the wake of unprecedented environmental challenges is the major cry of the day. This study aims to investigate the impacts of financial development, technological innovation, globalization, trade openness, and renewable energy consumption on the ecological footprint of 14 countries with the highest levels of financial development. The utilized econometrics battery include slope homogeneity tests, Westerlund cointegration, panel Augmented Mean Group (AMG), and Dumitrescu-Hurlin (2012) causality approaches. The study period spans from 1990 to 2018. The empirical outcomes indicate that financial development negatively affects environmental sustainability. The results further reveal that globalization technological innovation, trade openness, and renewable energy consumption bolster environmental quality. Based on the causality outcomes, a bidirectional causal link is witnessed between technological innovation, globalization, renewable energy consumption, and ecological footprint; however, a unidirectional causality relationship exists from trade openness and financial development to ecological footprint. The study findings underscore the importance of globalization, technological innovation, trade openness, and renewable energy consumption in fine-tuning environmental policies and improving environmental quality in these countries.